Respuesta :

Answer:

y = (1/60) x² - (7/20) x + 49/30

Step-by-step explanation:

equation formula:    y = ax² + bx + c

pass (-1,2) (2,1) (7,0)

(-1,2):  a - b + c = 2   ... (1)

(2,1):   4a + 2b + c = 1   ... (2)

(7,0):   49a + 7b + c = 0   ... (3)

(2)-(1):  3a + 3b = -1   ... (4)

(3)-(2):  45a + 5b = -1   ... (5)

(4)*15-(5): 40b = -14         b = - 7/20   ... (6)

(4): 3a = -1 - 3*(-7/20) = 1/20        a = 1/60    ...(7)

(1): c = 2 - 1/60 + (-7/20) = 49/30        c =  49/30

equation:  y = (1/60) x² - (7/20) x + 49/30

Ver imagen lynnkc2000